Results of Kidney Biopsies among Adult Iraqi Patients in a Single Center - Al-Saedi, Ali Jasim H.; Abdul Mahdi, Mohammad; Jameel, Nawar S. (AL-Kindy College Medical Journal, 2011)
Background: Patients requiring renal biopsies have various glomerular diseases according to their demographic characteristics. Objective: To study types of glomerular disease among adult Iraqi patients in a single center in Baghdad/Iraq Material and Methods: A total of 120 native kidney biopsies were studied. All biopsies were adequate and were processed for Light Microscopy. The age range of the study patients was 17-67 years, with a mean of 38.5 years. The mean follow up period was 28 weeks (4-52 weeks) Indication for biopsy included: Nephrotic syndrome (N=72; 60%), Asymptomatic proteinuria (N=21; 17.5%), acute nephritic presentation (N=17; 14.16%), asymptomatic haematuria (N=10; 8.33%). Results: Primary glomerulonephritis (GN) was seen in 102 of 120 patients (85%), focal segmental glomerulosclerosis, and membranous nephropathy were the most common histological diagnosis (33.3% and 21.5% respectively). Conclusion: The study further emphasize the need for national GN registry and long term follow up, to recognize the common pattern of GN, their natural history, the appropriate line of management, and to try to halt their progression to end stage renal disease (ESRD).